Reactive ion etching techniques for uncooled pyroelectric detectors - Landi, S (Cranfield University, 2005)
This research presents the design and microfabrication of a novel pyroelectric IR array detector. Micromachined concentrators are incorporated in the device to focus incoming radiation. Patterning of the sensing elements is introduced to reduce thermal losses. According to the physical theory of IR detection, these improvements can enhance the response of a pyroelectric detector. The device is designed to be fabricated using state of the art micro systems technology. The design and fabrication route build partially on a previous primitive version of the device, which has been used as a case study. An array of 3 - d structured non-imaging collectors is coupled to the sensing array. A survey of concentrators identified the most suitable contours, which were subsequently analysed. An original series of “suspended” collectors were especially developed for incorporation in this device. The calculations demonstrated that, generally, the Compound Parabolic Concentrator outperforms any other system. In all cases, truncated or suspended systems would show lower efficiency than the respective full systems. The search for a viable microfabrication route focussed on methodologies based on Deep Reactive Ion Etching. Experimental trials, using both 3 - d sacrificial masks and conventional binary masks demonstrated a range of interesting structures, some of which had not been previously showed in literature. Long etching cycles in pure SFg could only approximate a tenth of the ideal contour and lacked flexibility, but demonstrated the lowest surface roughness (300 nm to 2 /rm), highest reliability and are easy to implement and optimise. Being the processes of choice, these were analysed further and chosen as a quick route for producing working prototypes of the device. A chemical model of the process was built, based on mass balance considerations. Calculations demonstrated that, by isolating each sensing element of the array on a spiral microbridge, the responsivity of the device could be increased up to 100 times. Conventional Reactive Ion Etching was used for patterning the entire active layer (pyroelectric material and electrodes). Suspended spiral elements were successfully incorporated in the final prototypes. To produce the final device, two wafers (250 /rm thick) were stacked to approximate a collector with 37 % truncation, leading to a maximum theoretical collection efficiency of 2.36. The electrical properties and response from the prototypes were measured and the results compared with the theoretical performance of the device, calculated using rough approximations in 2 - d. Using a home made testing rig, the best responses obtained were between 5 to 25 mV. Unfortunately, the model used is not sophisticated enough to allow straightforward comparison with the experimental results. Recently, better agreement has been demonstrated using a 3 - d model.